Pengembangan Model Pembelajaran Pendidikan Karakter Berbasis Kearifan Lokal pada Mahasiswa Program Studi Perhotelan Politeknik Bosowa - Veronika, Riska; Andriani, Dewi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to recognize the differences in learning outcomes of students at the Perhotelan Politeknik Bosowa by using Local Wisdom based Character Education Learning Model. The research method applied R&D method with the ADDIE research model. The research stages applied were 1) Analysis, 2) Design, 3) Development, and 4) Implementation. This research was conducted at the Politeknik Bosowa with a sample of 20 Hospitality Study Program students. Data were collected using assessment instrument filled in by lecturers. This research used quantitative and qualitative analysis. Based on the results of the validity test, the instruments and products developed were in the valid category. The instruments and products developed were validated by experts. Based on the results of observations of student activities in applying 3S cultural local wisdom, the results of the student assessment were in a good category. Thus, the results of the assessment indicated that students had been able to implement the 3S concept when attending practical classes in the course of cake and bread processing at Politeknik Bosowa.